2015
DOI: 10.1158/1940-6207.capr-14-0267
|View full text |Cite
|
Sign up to set email alerts
|

High-Density Lipoprotein-Cholesterol, Daily Estradiol and Progesterone, and Mammographic Density Phenotypes in Premenopausal Women

Abstract: High-density lipoprotein-cholesterol (HDL-C) may influence the proliferation of breast tumor cells, but it is unclear whether low HDL-C levels, alone or in combination with cyclic estrogen and progesterone, are associated with mammographic density, a strong predictor of breast cancer development. Fasting morning serum concentrations of HDL-C were assessed in 202 premenopausal women, 25 to 35 years of age, participating in the Norwegian Energy Balance and Breast Cancer Aspects (EBBA) I study. Estrogen and proge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 53 publications
2
6
0
Order By: Relevance
“…HDL-C and percent density were also inversely associated in a small sample of postmenopausal women [26]. In contrast, other studies have reported positive associations between HDL-C levels and mammographic density in premenopausal women [25, 43, 44], as well as null associations in premenopausal [22] and postmenopausal women [24, 27]. Most, but not all [45, 46, 38], studies of HDL-C and breast cancer risk support a protective effect for high HDL-C although results across BMI categories and menopausal status have been inconsistent [4751, 3].…”
Section: Discussionmentioning
confidence: 96%
“…HDL-C and percent density were also inversely associated in a small sample of postmenopausal women [26]. In contrast, other studies have reported positive associations between HDL-C levels and mammographic density in premenopausal women [25, 43, 44], as well as null associations in premenopausal [22] and postmenopausal women [24, 27]. Most, but not all [45, 46, 38], studies of HDL-C and breast cancer risk support a protective effect for high HDL-C although results across BMI categories and menopausal status have been inconsistent [4751, 3].…”
Section: Discussionmentioning
confidence: 96%
“…14 Low HDL may be associated with higher estrogen levels and absolute mammographic intensity. [15][16][17] In addition, different lipoproteins show that the effect of HDL-cholesterol on breast cancer prognosis is different from the lower breast cancer phenotype, 18 according to progesterone receptor expression. 19 The relation between serum lipids levels and breast cancer risk is unclear; because cholesterol is the precursor to sex steroid hormones, higher levels of cholesterol could possibly increase risk of breast cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, low levels of HDL have been associated with increased levels of low-grade inflammation and proinflammatory cytokines [ 9 13 ], which in turn induce higher local estradiol levels and breast cell proliferation [ 14 , 15 ]. We have recently observed that HDL-C levels, either alone or in combination with high levels of estrogen or progesterone, were associated with mammographic density phenotypes [ 16 ]. Moreover, lipid molecules have been shown to influence inflammation [ 9 , 10 ], one of the hallmarks in cancer and breast cancer development [ 17 ] and prognosis [ 18 ], and elevated biomarkers of inflammation are associated with reduced survival among breast cancer patients.…”
Section: Introductionmentioning
confidence: 99%